HUBUNGAN KADAR MIKROALBUMIN TERHADAP KADAR UREUM DAN KREATININ PADA PASIEN DIABETES MELLITUS TIPE 2 DI PUSKESMAS CILACAP TENGAH 1 - Hastuti Budi Rahayu; Meka Faizal Farabi; Dini Puspodewi (Klinikal Sains : Jurnal Analis Kesehatan, 2026)
Diabetes Mellitus is a serious, long-term condition that occurs when a person's blood glucose levels rise because the body cannot produce enough insulin. According to the International Diabetes Federation (IDF), there were approximately 20.4 million adults aged 20-79 years old with diabetes in Indonesia in 2024, and this number is expected to increase to 28.6 million by 2050. Diabetic nephropathy is a complication of diabetes mellitus that begins with microalbuminuria, which can be detected before kidney function declines, indicated by increased blood urea and creatinine levels. This study aims to determine the relationship between microalbuminuria and serum urea and creatinine levels in patients with type 2 diabetes mellitus  Method: This research is descriptive with a cross-sectional research design using medical record data from patients participating in the Chronic Disease Management Program (Prolanis) at the  Central Cilacap 1 Puskesmas in the period of April 2025. Data were analyzed using the Kolmogorov-Smirnov normality test and continued using the Spearman non-parametric correlation test. Result: The results of the study showed that the average microalbumin level was 122.9491 mg/g creatinine, the average urea level was 28.60 mg/dL and the average creatinine level was 0.91 mg/dL. The results of the Spearman correlation test showed a significant value (ρ-value) between microalbumin and urea levels of 0.003 and between microalbumin and creatinine levels of 0.003. he ρ-value of each is <0.05 Conclusion: can be concluded that there is a relationship between microalbumin levels and urea and creatinine levels in type 2 Diabetes Mellitus patients at the Central Cilacap 1 Puskesmas